Daily Use of Energy Management Strategies and Occupational Well-being: The Moderating Role of Job Demands - Parker, Stacey L. (Front Psychol, 2017)
We examine the relationships among employees’ use of energy management strategies and two occupational well-being outcomes: job satisfaction and emotional exhaustion. Based on conservation of resources theory, it was hypothesized that employees with high job demands would benefit more from using energy management strategies (i.e., including prosocial, organizing, and meaning-related strategies), compared to employees with low job demands. We tested this proposition using a quantitative diary study. Fifty-four employees provided data twice daily across one work week (on average, 7 daily entries). Supporting the hypotheses, prosocial energy management was positively related to job satisfaction. Moreover, employees with high job demands were less emotionally exhausted when using prosocial strategies. Contrary to predictions, when using organizing strategies, employees with low job demands had higher job satisfaction and lower emotional exhaustion. Under high job demands, greater use of organizing strategies was associated with lower job satisfaction and higher emotional exhaustion. Finally, use of meaning-related strategies was associated with higher emotional exhaustion when job demands were low. With this research, we position energy management as part of a resource investment process aimed at maintaining and improving occupational well-being. Our findings show that this resource investment will be more or less effective depending on the type of strategy used and the existing drain on resources (i.e., job demands). This is the first study to examine momentary effects of distinct types of work-related energy management strategies on occupational well-being.